2010
DOI: 10.1123/apaq.27.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Level and Gross Motor Performance of Children With Attention-Deficit Hyperactivity Disorder

Abstract: The purpose of this study was to assess fitness and gross motor performance of children with ADHD, including users and nonusers of methylphenidate medication. Seventy boys took part in the study. Fitness level of children with ADHD using medication or not, including body composition, flexibility, and muscular endurance, was similar to that of a control group. The only difference was observed for body mass index, which was lower in children with ADHD using medication. Aerobic capacity was also similar when meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
1
27
1
3
Order By: Relevance
“…Verret et al (2010a) studied the effects of a moderate-to high-intensity physical exercise program on fitness, cognitive functioning and ADHD symptoms in 21 ADHD children (age range: 7-12, mean = 9.1 years). Their findings indicated that the physical exercise program improved muscular capacity, motor skills, parent-teacher behavior reports, and levels of information processing (see also Verret et al 2010b). In 75 healthy older individuals, Flöel et al (2010) have shown that physical activity, but not cardiovascular fitness, was linked to better memory encoding after controlling for age, sex, education, depression, alcohol consumption, and smoking.…”
Section: Physical Exercise Interventionmentioning
confidence: 92%
“…Verret et al (2010a) studied the effects of a moderate-to high-intensity physical exercise program on fitness, cognitive functioning and ADHD symptoms in 21 ADHD children (age range: 7-12, mean = 9.1 years). Their findings indicated that the physical exercise program improved muscular capacity, motor skills, parent-teacher behavior reports, and levels of information processing (see also Verret et al 2010b). In 75 healthy older individuals, Flöel et al (2010) have shown that physical activity, but not cardiovascular fitness, was linked to better memory encoding after controlling for age, sex, education, depression, alcohol consumption, and smoking.…”
Section: Physical Exercise Interventionmentioning
confidence: 92%
“…These findings agree with those of Verret et al . () who reported that health‐related fitness, including muscle endurance and flexibility, was not different in ADHD children with or without MPH treatment and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…() suggested that MPH could improve both attention and motor coordination in children with ADHD. In a comparison of fitness levels, body mass index was lower in ADHD children treated with MPH than in those who did not receive the drug (Verret et al ., ). ADHD children also demonstrate deficits in locomotive movement skills compared with healthy subjects (Verret et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Both human and animal studies strongly support the impact of exercise on improved cognitive function [83]. Exercise has been found to improve executive function and increase prefrontal activation during executive function tasks in children [84•], and some initial work has documented that exercise in children with ADHD has yielded improvements in overall behavior, sustained attention, vigilance, and impulsivity [85,86]. Exercise increases brain-derived neurotrophic factor, a molecule involved in synaptic plasticity, learning, and memory, which may be particularly important for individuals with ADHD [83].…”
Section: Exercisementioning
confidence: 99%